Structure-Based Virtual Screening and Molecular Docking on the Indonesian Herbal Compound as a Promising Insulin Receptor (INSR) Inhibitor to Suppress Tumor Growth - Candraningrum, Veronica Hesti; Erlina, Linda; Paramita, Rafika Indah; Fadillah, Fadillah; Dwira, Surya; Fatriansyah, Jaka Fajar (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
A healthy cell maintains a homeostasis condition of glucose level, whereas cancer cells do not. Increased glucose uptake is a hallmark of cancer cells that helps them survive, proliferate, and spread. INSR is one of key feature that take part in glucose metabolism through insulin signaling. To block the entry of glucose into cells, researchers were aiming to disrupt the insulin signaling pathway as the upstream activation in glucose metabolism by inhibiting insulin receptor (INSR) using Indonesian herbal compounds. The approach during the screening was structure-based drug discovery (SBDD) method where INSR was determined as the macromolecules. Some parameters such as binding affinity, constant inhibition, drug-likeness, pharmacokinetics, and toxicity were applied to help the search of potential inhibitor. According to the test results, Heterophylin, Sanggenofuran A, and Epigallocatechin-3-O-caffeate had the strongest molecular binding activity against the INSR protein. Heterophylin is discovered in jackfruit fruit trees and Sanggenofuran A is present in mulberry trees. While Epigallocatechin-3-O-caffeate, is abundantly found in green tea plant